The quotient rule says that if $u$ and $v$ are functions of $x$ then
\[\simplify[std]{Diff(u/v,x,1) = (v * Diff(u,x,1) - u * Diff(v,x,1))/v^2}\]
a)
For this example:
\[\simplify[std]{u = sin({a}x)}\Rightarrow \simplify[std]{Diff(u,x,1) = {a}cos({a}x)}\]
\[\simplify[std]{v = {b}sin({a}x)+{c}cos({a}x)} \Rightarrow \simplify[std]{Diff(v,x,1) = {a*b}cos({a}x)+{-a*c}sin({a}x)}\]
Hence on substituting into the quotient rule above we get:
\[\begin{eqnarray*} \frac{df}{dx}&=&\simplify[std]{({a}cos({a}x)({b}sin({a}x)+{c}cos({a}x))-sin({a}x)({a*b}cos({a}x)+{-a*c}sin({a}x)))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({a*b} cos({a}x) sin({a}x)+{a*c} cos({a}x)^2-{a*b} sin({a}x)cos({a}x)+{a*c}sin({a}x)^2)/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({a*c}cos({a}x)^2+{a*c}sin({a}x)^2)/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({a*c}(cos({a}x)^2+sin({a}x)^2))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({a*c})/({b}sin({a}x)+{c}cos({a}x))^2} \end{eqnarray*}\]
Hence $a=\var{a*c}$
b)\[\simplify[std]{u = cos({a}x)}\Rightarrow \simplify[std]{Diff(u,x,1) = -{a}sin({a}x)}\]
\[\simplify[std]{v = {b}sin({a}x)+{c}cos({a}x)} \Rightarrow \simplify[std]{Diff(v,x,1) = {a*b}cos({a}x)+{-a*c}sin({a}x)}\]
Hence on substituting into the quotient rule above we get:
\[\begin{eqnarray*} \frac{dg}{dx}&=&\simplify[std]{({-a}sin({a}x)({b}sin({a}x)+{c}cos({a}x))-cos({a}x)({a*b}cos({a}x)+{-a*c}sin({a}x)))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({-a*b}sin({a}x)^2-{a*c} sin({a}x)cos({a}x)-{a*b}cos({a}x)^2+{a*c}sin({a})cos({a}x))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({-a*b}sin({a}x)^2-{a*b}cos({a}x)^2)/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({-a*b}(sin({a}x)^2+cos({a}x)^2))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{({-a*b})/({b}sin({a}x)+{c}cos({a}x))^2} \end{eqnarray*}\]
Hence $b=\var{-a*b}$
c)
We have that $h(x)=\simplify[std]{{m}f(x)+{n}g(x)}$
Hence \[\begin{eqnarray*}\frac{dh}{dx} &=& \simplify[std]{{m}*Diff(f,x,1)+{n}*Diff(f,x,1)}\\ &=&\simplify[std]{{m}*({a*c}/({b}sin({a}x)+{c}cos({a}x))^2)+{n}({-a*b}/({b}sin({a}x)+{c}cos({a}x))^2)}\\ &=&\simplify[std]{(({m}*{a*c})+({n}*{-a*b}))/({b}sin({a}x)+{c}cos({a}x))^2}\\ &=&\simplify[std]{{res}/({b}sin({a}x)+{c}cos({a}x))^2} \end{eqnarray*}\]
Hence $c=\var{res}$